Increasing student engagement and retention using online learning activities wikis, blogs and webquests - Wankel, Laura A.; Blessinger, Patrick (Cutting-edge technologies in higher education ;, 2012)
Increasing Student Engagement and Retention using Social Technologies: Facebook, e-portfolios and other Social Networking Services uses case studies, surveys, and literature reviews to examine how these social media technologies are being used to improve writing and publishing skills in students, create engaging communities of practice, and how these tools are being used for e-Mentoring and constructing online reputations. Chapters include applying positive psychology and cognitive styles in user design, designing outcome based curricula using student personality types, engaging second language students through electronic writing tasks, applying psychological variables on the academic use of social media, using social media to motivate students to take charge of their own learning processes, and creatively using technology to enhance teacher education. This volume will also discuss a framework for deploying and assessing these technologies in higher education institutions.